2013
DOI: 10.2527/jas.2012-6114
|View full text |Cite
|
Sign up to set email alerts
|

2011 AND 2012 EARLY CAREERS ACHIEVEMENT AWARDS: Farm and pig factors affecting welfare during the marketing process1,2

Abstract: The objective of this paper is to review the scientific literature to identify on-farm factors that contribute to market weight pig transportation losses. Transportation of market weight pigs is an essential element to the multisite pork production model used in the United States. In 2011 alone, approximately 111 million market weight pigs were transported from the finishing site to the abattoir. For pigs, the marketing process can present a combination of potentially novel, physical, and/or unfamiliar experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
0
28
0
2
Order By: Relevance
“…La mayoría de los cerdos de ceba son transportados en camiones desde la granja hasta la planta de sacrificio, donde gran parte de ellos llega y se procesa sin incidentes. Sin embargo, un pequeño porcentaje de animales mueren y otros presentan dificultad para caminar durante el desembarque, lo que se conoce comúnmente como «cerdos no ambulatorios» (Sutherland et al, 2009a;Johnson et al, 2013). La presencia de cerdos no ambulatorios o que mueren en cualquier etapa durante el proceso de comercialización se denominan «pérdidas por transporte» (Berry et al, 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…La mayoría de los cerdos de ceba son transportados en camiones desde la granja hasta la planta de sacrificio, donde gran parte de ellos llega y se procesa sin incidentes. Sin embargo, un pequeño porcentaje de animales mueren y otros presentan dificultad para caminar durante el desembarque, lo que se conoce comúnmente como «cerdos no ambulatorios» (Sutherland et al, 2009a;Johnson et al, 2013). La presencia de cerdos no ambulatorios o que mueren en cualquier etapa durante el proceso de comercialización se denominan «pérdidas por transporte» (Berry et al, 2012).…”
Section: Introductionunclassified
“…Los cerdos fatigados exhiben un comportamiento alterado caracterizado por la presencia de dificultad respiratoria (jadeo), decoloración de la piel, o ambos. Si el estrés no se elimina o si se encuentran factores estresantes adicionales, el cerdo se mostrará reacio a moverse, con vocalizaciones anormales, desarrollo de temblores musculares o manifestará una combinación de indicadores de estrés (Ritter et al, 2009a;Johnson et al, 2013). Los cerdos fatigados presentan acidosis metabólica como respuesta al manejo y al transporte (Ritter et al, 2006), con-dición que puede dar como resultado una reducción de 0.5 unidades del pH sanguíneo y aumento de la temperatura corporal de 1.0-2.5 °C (Aradom et al, 2012).…”
Section: Introductionunclassified
“…A survey by researchers at Iowa State University at fifteen pig buying stations that purchase both market weight pigs and sows and boars showed that sows and boars were 86% of the non-ambulatory fatigued animals and 73% of the lame animals [17]. In the total population, which included market weight pigs, fatigued pigs equaled 16% and lame pigs only 5% [2]. Sows and boars were 82% of the animals with a body condition score of 1 and only 4% of the total population had a body condition score of 1 [17].…”
Section: Reasons For Removing Boars and Sows From The Breeding Herdmentioning
confidence: 99%
“…Numerous papers have been written that cover market pig welfare during transportation [1,2,3,4,5] but little attention has been given to cull sows and boar fitness to transport. Cull sow and boar handling and transport can be quite variable in that standard practices have not been adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lack of functional sweat glands (Fox et. al., 2013;Johnson et. al., 2013;Warriss et al, 2006), pigs are particularly susceptible to the effects of environmentally-induced heat stress (HS), which can result in production losses as well as morbidity and mortality (Johnson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%